Lymphangioma of the fetal neck within the PIK3CA‐related‐overgrowth spectrum (PROS): A case report. Issue 7 (21st July 2021) - Scharf, Jann Lennard; Gembicki, Michael; Dracopoulos, Christoph; Hellenbroich, Yorck; Offermann, Anne; Stichtenoth, Guido; Tafazzoli‐Lari, Kianusch; Tharun, Lars; Weichert, Jan
Abstract: The delineation of the prenatal diagnostic key features of PIK3CA‐related overgrowth spectrum disorders will assume a crucial part in future and a prenatal diagnosis of the causing mutations would provide physicians with a simplified interdisciplinary perinatal management. Abstract : The delineation of the prenatal diagnostic key features of PIK3CA‐related overgrowth spectrum disorders will assume a crucial part in future and a prenatal diagnosis of the causing mutations would provide physicians with a simplified interdisciplinary perinatal management.